Making Progress: Ellison, Rinehart, and the Critic - Cheryl Alison (European Journal of American Studies)
Since Ralph Ellison’s death, the draft materials of his second, unfinished novel have become available, in addition to his notes for Invisible Man (1952). This article encourages literary interpreters to exercise restraint in retroactively imposing narrative order and coherence upon the author’s incomplete work and working materials. Taking as an example the character Rinehart, who appears in varying forms throughout Ellison’s career, this article traces and interrogates the character’s treatment in the work of exemplary Ellison critic Adam Bradley to demonstrate that the urge to create a linear interpretive model diminishes not just the character but also Ellison’s considerable nuance. Focused character interpretation ultimately makes the larger case that coming to Ellison’s archive, as well as his published works, requires flexibility adequate to the author’s own mobile habits of thought and composition.